EFFECT OF ADDITIONAL LEAF EXTRACT OF CIPLUKAN (Physalis angulata L) ON FEED ON THE GROWTH PERFORMANCE OF TILAPIA (Oreochromis niloticus) - Suaebatul Aslamiah; Fariq Azhar; Muhammad Marzuki (Aquaculture Department, University of Mataram, 2021)
The purpose of this study is to determine the effect of the effectiveness of the addition of ciplukan leaf extract (Physalis angulata L.) on feed to the growth performance of tilapia (Oreochromis niloticus). This research method uses a Complete RandomIzed Design (RAL). This study consisted of 4 treatments and 3 replays, so 12 experimental units were used. Dose treatment on P0 (feed without the addition of ciplukan leaf extract), P1 (Feed added ciplukan leaf extract with a dose of 4%), P2 (Feed added ciplukan leaf extract with a dose of 8%), and P3 (Feed added ciplukan leaf extract with a dose of 12%). This dosage treatment is based on Effendi &Hardi research (2014) with dose treatment of 4%, 8%, and 12% per 1kg of feed. the addition of ciplukan leaf extract with a concentration of 8% in feed provides absolute weight growth of (37.39±20.33), survival rate of (83.33±0.9 8), daily growth rate (1.25±0.60), and feed utilization efficiency of (4.67±0.58) and tend to be higher than other treatments.